Can energy conservation and emission reduction policies affect household carbon emissions? Evidence from China - Luo, Juan; Yang, Jiwen; Wan, Siyu; Zhao, Jiaqi; Liang, Jing (Frontiers in Energy Research, 2023)
This article investigates the impact of energy conservation and emission reduction policies on household carbon emissions by using the fixed-effect model and finds energy conservation and emission reduction policy has a positive effect on household carbon emissions. The data sample covers 31 provinces, autonomous regions and municipalities in China from 2011 to 2020. In addition, this article conducts a mechanism test and finds new energy public buses can play a negative mediating effect on the relationship between government policy and household carbon emissions. Besides, this article finds that the effect of energy conservation on emission reduction policies is more evident in western areas.